Adaptation elements in African Nationally Determined Contributions (NDCs) and National Adaptation Plans (NAPs) - Nowak, Andreea C.; Njuguna, Lucy; Crumpler, Krystal (2023)
The dataset contains information on climate hazards, systems at risk, adaptation goals, adaptation objectives, adaptation actions, and adaptation indicators included in African Nationally Determined Contributions (NDCs) and National Adaptation Plans (NAPs) (2023-11-7)